What we carry, keep, and create: an urban intertribal community’s survivance storywork navigating K-12 Indian education - Bonilla, Jennifer Lyn (My University, 2025)
This qualitative study employs survivance storywork methods to document the stories of American Indian/Alaska Native families and community members’ engagement with the Title VI and Johnson O’Malley (i.e., Indian Education) programs in the intertribal community of Lawrence, Kansas. This study collects and synthesizes the stories of these families to deepen our understanding of the ways this intertribal community mobilizes, navigates, and builds sustainable action within the context of Indian Education programs housed in a Eurocentric public education system. The findings and the recommendations of the study are presented through arts-based and Indigenous storywork using modalities of poetry and storytelling, along with inter-woven personal reflections and stories from the author as a member of this community. Built around the themes of what the participant storytellers carry, keep, and create, the storytellers from this intertribal community reveal the value of relationality, culturally sustaining practices, intergenerational collaboration, and sustained advocacy from intertribal communities in a manner that actively and intentionally build futures for Indigenous children. This study concludes with a creative exploration around sweetgrass, and how it might offer a useful metaphor for understanding and describing how community building unfolds through educational programing when operating in a unique urban intertribal environment.
Keywords: Survivance storywork; Urban intertribal; Indian education; Indigenous education; Title VI; Johnson O'Malley